Hollow-core anti-resonant double-ring nested negative-curvature fiber for 0.3THz-0.5THz transmission - Fu, Zhenwei (My University, 2021)
The terahertz (THz) domain is an electromagnetic wave with a frequency in the range of 0.1THz to 10THz lying between microwave and infrared spectra, which have great potential in public security and communication. Although terahertz equipment, terahertz sensing, and terahertz imaging systems already exist on the business market, and terahertz wireless communication has been performed, it still takes a lot of time to develop efficient and low loss terahertz components (terahertz sources, terahertz detectors, and terahertz fibers). The 2019 world radiocommunication conference (WRC-19) finally approved 137GHz bandwidth resources for mobile service applications, where the bandwidth is distributed in four frequency bands: 275GHz-296GHz, 306GHz-313GHz, 318GHz-333GHz, and 356GHz-450GHz.This thesis mainly investigates terahertz transmission via the anti-resonant reflecting optical waveguiding (ARROW) mechanism with the terahertz hollow-core anti-resonant fiber(HC-ARF) with single ring and the terahertz HC-ARF with double ring in the range of 0.3 THz-0.5 THz. We proposed a novel hollow-core anti-resonant fiber called hollow-core anti-resonant double-ring nested negative-curvature fiber (HC-DRN-NCF) in the transmission bandwidth 0.3THz-0.5THz. This thesis demonstrates how the confinement loss is influenced by the geometrical structure parameter. The novel fiber hollow-core anti-resonant double-ring nested negative-curvature fiber (HC-DRN-NCF) achieves broad transmission bandwidth, bending improved performance, and effectively single-modedness transmission at 0.3 THz-0.5 THz. This fiber could further investigate and apply to the field as data transmission, gas sensing, power delivery, and provides a series of design guidelines for different fiber application scenarios.
Keywords: Hollow-core anti-resonant fiber, Terahertz, Confinement loss, Bending loss, Single-modedness